Forecast Model of Prices for Liquefied Natural Gas in the World Asian Energy Market - Lvovich Elyakov, Alexander; Damdinovna Elyakova, Izabella; Alekseevich Pakhomov, Alexandr (International Journal of Criminology and Sociology, 2022)
The relevance of the study lies in the fact that concerning the strategic objectives of Russia to take a share of the growing world market of liquefied natural gas, it is advisable to assess the impact of factors affecting the development of the global liquefied natural gas market. This article provides a comparative analysis of exports and imports in the global LNG market by region, identifies potential trends in the development of global LNG trade over the past 50 years, it makes a price forecast for liquefied natural gas (LNG) for the Asia-Pacific region (APR) based on a correlation and regression analysis of the dependence of LNG prices on changes in factors such as world oil prices, global demand for LNG, exchange rates and growth rates of the Asia-Pacific economies.